ENHANCING ELEMENTARY STUDENTS' MOTIVATION AND PARTICIPATION IN MATHEMATICS LEARNING THROUGH WORDWALL: A CASE STUDY - Nur Khosiah; Imro Atus Soliha (Universitas Islam Negeri Mataram, 2025)
This study aims to enhance students’ motivation and participation in elementary mathematics learning by utilising the interactive digital media “Wordwall” as an alternative solution to the low levels of student interest and engagement in a subject often perceived as complex and less appealing. The research employed a qualitative approach with a case study design, using data collection techniques such as observation, interviews, and documentation. The data were analysed descriptively through the stages of data reduction, data display, and conclusion drawing. The informants consisted of the principal, teachers, and fourth-grade students at MI Darus Sholihin, Boto District, Probolinggo Regency. The results of the study indicate that the use of Wordwall media effectively increased students’ motivation and participation in mathematics learning. This is evidenced by the increased number of students who actively asked questions, responded, engaged in discussions, and interacted during the learning process. Moreover, the classroom atmosphere became more conducive, enjoyable, and interactive. Thus, the implementation of Wordwall media serves as an innovative strategy to improve the quality of mathematics learning in elementary schools